Cocaine exposures reported to United States poison control centers, 2000–2020. (3rd July 2022) - Becker, Sarah; Spiller, Henry A.; Badeti, Jaahnavi; Funk, Alexandra R.; Casavant, Marcel J.; Zhu, Motao; Michaels, Nichole L.; Smith, Gary A.
Abstract: Objective: To investigate characteristics of cocaine exposures reported to US Poison Control Centers. Methods: Data from the National Poison Data System regarding cocaine-related calls to regional poison control centers from January 1, 2000 to December 31, 2020 were analyzed. Results: There were 59, 466 first-ranked cocaine-related calls managed by poison control centers during the study period. Males accounted for more than two-thirds (70.3%) of these cases. The 20–29-year-old age group had the highest cocaine exposure rate, followed by 30–39-year-olds. Admission to a health care facility (HCF) occurred in 38.9% of cases and 41.1% of individuals had a serious medical outcome. Serious medical outcome (OR: 1.50, 95% CI: 1.39–1.61) and admission to a HCF (OR: 1.12, 95% CI: 1.06–1.19) were more likely to occur among individuals 13 years or older than among individuals <13 years old. Cocaine exposures involving additional substances were more likely to lead to a serious medical outcome (OR: 2.22, 95% CI: 2.14–2.29) and admission to a HCF (OR: 2.52, 95% CI: 2.43–2.61) than exposures to cocaine alone. Overall, the proportion of exposures resulting in a serious medical outcome increased from 39.9% in 2000 to 60.4% in 2020 ( p < 0.0001). Likewise, the proportion of exposures resulting in admission to a HCF increased from 49.1% in 2000 to 54.4% in 2020 ( p < 0.0001). There was also an increase in the rate of fatal cocaine cases from 2012 to 2020, driven by multiple-substance exposures. Conclusions: Cocaine exposures are a serious public health problem associated with substantial morbidity and mortality. The severity of cocaine exposures increased during the study period, reflected in an increased rate of fatal cocaine exposures since 2012 and increased proportions of serious medical outcomes and cases requiring admission to a health care facility. Additional efforts to prevent initiation of cocaine use and treat addiction among high-risk groups should be undertaken.